Paradigmatic Piety: Liturgy in the Life of Martha, Mother of Symeon Stylites the Younger - Parker, L (John Hopkins University Press, 2016)
The Life of Martha, the mother of the sixth-century stylite Symeon the Younger, has been almost completely neglected in modern scholarship. Yet the text possesses considerable historical interest as evidence for the contested development of a cult, as a literary composition with a unique structure, and as the Life of a holy woman who was neither a martyr nor a nun. Martha’s hagiographer eschews most traditional emphases of the Lives of female saints, such as celibacy and asceticism, presenting instead an original, inclusive vision of piety focused on participation in liturgy and the sacraments.